2018
DOI: 10.4028/www.scientific.net/kem.763.694
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Performance of Braces with Different Support Connections in Special Concentrically Braced Frames

Abstract: Gusset plate connections between the steel braces and the supporting frame members play an important role in the performance of special concentrically braced frames (SCBFs) under earthquake loading conditions. Extensive studies have been conducted on SCBFs in which the gusset plate connections are designed to ensure the out-of-plane buckling of steel braces. However, research on the cyclic behavior of gusset plate connections allowing the in-plane buckling of braces is very limited. An experimental investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…They used an elliptical end distance instead of a linear one and found that the elliptical end distance of 8tp provided the highest ductility and deformation capacity, consequently delaying and limiting failure in welds or braces. Patra et al [19], in 2018, conducted a series of experimental and numerical studies to investigate the effect of brace end connection type on brace behavior. They used a gusset-knife plate for out-of-plane rotation and a thick plate for in-plane rotation of the brace.…”
Section: Fig 1 Conventional Configurations Of Concentrically Braced F...mentioning
confidence: 99%
“…They used an elliptical end distance instead of a linear one and found that the elliptical end distance of 8tp provided the highest ductility and deformation capacity, consequently delaying and limiting failure in welds or braces. Patra et al [19], in 2018, conducted a series of experimental and numerical studies to investigate the effect of brace end connection type on brace behavior. They used a gusset-knife plate for out-of-plane rotation and a thick plate for in-plane rotation of the brace.…”
Section: Fig 1 Conventional Configurations Of Concentrically Braced F...mentioning
confidence: 99%
“…Reinforcement plate of sizes 10 mm thickness and dimension 40x130 mm was used on both side as well as on both the end of the connections. In case of outof-plane buckling (OOPB) connections, the dimension of the gusset plate mostly depends on clearance for which it is design for [15,16]. The interface of the connection of the sub-assemblage system was design using the AISC 341-16 [12].…”
Section: Details Of the Test Programmentioning
confidence: 99%
“…[8]. The design modification was carried out such that secondary hinges will form in the knife plate, and gusset plate was designed to remain elastic [9][10][11][12].…”
Section: Balanced Design Procedures (Bdp)mentioning
confidence: 99%
“…demand based on the type of the connection [5] provided to the system. The connection of the SCBF system is generally divided into three types:…”
Section: Introductionmentioning
confidence: 99%